Reducing Embodied Carbon of Paving Blocks with Landfill Waste Incineration Ash: An Eco-Cement Life Cycle Assessment - Darhamsyah, .; Tumpu, Miswar; Samawi, M. Farid; Anda, Martin; Abas, Azlan; Satria, M. Yusuf (Engineering, Technology & Applied Science Research, 2025)
This study examines the embodied carbon of paving blocks by substituting Portland Composite Cement (PCC) with landfill waste incineration ash at 0%, 25%, 50%, 75%, and 100% replacement levels. Using Life Cycle Assessment (LCA) and mechanical testing, the embodied carbon value was calculated per ISO 14040 standards. Results show that a 50% replacement achieves a 33% reduction in embodied carbon (120 kgCO₂e/m³ vs. 180 kgCO₂e/m³ for conventional paving blocks) while maintaining compressive strength within SNI criteria. These findings highlight the potential for eco-cement paving blocks to support sustainable construction and inform policies promoting low-carbon building materials.